(untitled) (Web of Teachers: Inderscience Research, 2025)
The article examines the process of formation and institutionalization of hospital education in the Republic of Uzbekistan in the context of developing an inclusive learning system. Special attention is given to the analysis of the activities of the Mehrli maktab hospital school, which became the first model of systemic interaction between educational and medical institutions. The study shows that hospital education serves not only a compensatory but also a rehabilitative and socially supportive function, contributing to the continuity of education for children undergoing long-term treatment. The article identifies issues related to regulatory framework development, staffing, and interdepartmental coordination, and offers practical recommendations for improving the organizational and pedagogical mechanisms of hospital education.